Learning from comparative ethnographic studies of early childhood education and care. Issue 3 (3rd July 2022) - Tobin, Joseph
ABSTRACT: International comparative ethnographic studies of ECEC (Early Childhood Education and Care) are difficult to conduct but worth the effort. Comparative studies featuring thick description and polysemic interpretations can challenge taken-for-granted assumptions, expand the menu of the possible, expose the provincialism of national approaches, and illuminate the global circulation of ECEC practices and ideas. Based on reflections on four major comparative international studies I have led, in this paper I describe effective strategies for conducting comparative ethnographic research in ECEC settings, explicate the rationale for doing so, and provide examples of how this approach can impact research, practice, and policy. Issues I address include the rationale for selecting countries for comparison, the formation of a research team, and distributing interpretive voice and power.